2003
DOI: 10.1016/s0168-0102(03)00029-4
|View full text |Cite
|
Sign up to set email alerts
|

Release from GABAA receptor-mediated inhibition unmasks interlaminar connection within superior colliculus in anesthetized adult rats

Abstract: The superior colliculus (SC) contains two major subdivisions, the superficial layers (sSC) and the deeper layers (dSC). sSC receives visual information from the retina and visual cortex, while dSC sends descending projections to the brainstem and spinal cord. It has not been clear whether and how sSC directly activates dSC, however recent studies in slice preparations reported that electrical stimulation of sSC induces burst firing in dSC neurons after application of bicuculline. In the present study, we teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…A previous study of anesthetized rats from our laboratory (Katsuta and Isa, 2003) showed that electrical stimulation of the optic fibers at 2 mA, which activated both Y and W fibers, induced negative field responses in the most dorsal part of the sSC, whereas a reversed positive potential was observed in the ventral part of the sSC and in the dSC. Such a current sink and source relationship might be derived from neurons with cell bodies in the ventral part of the sSC or in the dSC and dendritic arborizations in the dorsal part of the sSC that receive input from the optic tract.…”
Section: Field Potential Recordings In Sc Slicesmentioning
confidence: 83%
See 1 more Smart Citation
“…A previous study of anesthetized rats from our laboratory (Katsuta and Isa, 2003) showed that electrical stimulation of the optic fibers at 2 mA, which activated both Y and W fibers, induced negative field responses in the most dorsal part of the sSC, whereas a reversed positive potential was observed in the ventral part of the sSC and in the dSC. Such a current sink and source relationship might be derived from neurons with cell bodies in the ventral part of the sSC or in the dSC and dendritic arborizations in the dorsal part of the sSC that receive input from the optic tract.…”
Section: Field Potential Recordings In Sc Slicesmentioning
confidence: 83%
“…The circuits that organize this activity have been studied in vitro in slice preparations (for review, see Isa and Saito, 2001;Grantyn et al, 1984;Lee et al, 1997Lee et al, , 2007Isa et al, 1998;Meredith and Ramoa, 1998;Lo and Mize, 2000;Schmidt et al, 2001;Isa, 2002;Isa and Sparks, 2006;Neale and Salt, 2006;Kaneda et al, 2008). Furthermore, profiles of field potential responses at different depths evoked by sSC stimulation were measured by single-electrode recordings in anesthetized rats (Katsuta and Isa, 2003) and monkeys (Nikitin and Isa, 2004). However, these studies were performed using whole-cell recordings from individual neurons or field recording in one plane; hence, the information about the spatial and temporal properties of the whole population of dSC cells remained indirect and limited Isa, 2004, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Intracollicular injections of bicuculline (0.5 μl; 0.5 μl/min) were made with a 10 μl Hamilton syringe (Scientific Laboratory Supplies Ltd., Nottingham, UK) mounted on an infusion pump, connected to the needle by a length of plastic tubing. The experimental rationale in the present study was based on the important observation of Katsuta and Isa (2003) that local intra-collicular injections of bicuculline can reinstate visual sensitivity to the SC deep layers rendered insensitive by urethane anesthesia. (Note: Throughout the current article, we adhere to the convention of referring to all SC layers underlying the superficial layers as the ‘deep layers’).…”
Section: Methodsmentioning
confidence: 99%
“…Suffice it to say that it involves massive inhibitory interactions, both intrinsic to the colliculus (Katsuta and Isa, 2003) and coming from outside in the form of powerful inhibitory projections from several sources, only one of which is the already mentioned nigral projection. They include the zona incerta, anterior and posterior pretectal nuclei, the periparabigeminal area, a “critical zone” of the pedunculopontine region, and indirectly, via collicular interneurons, the parabigeminal nucleus (Ficalora and Mize, 1989; Appell and Behan, 1990; Behan and Appell, 1992; May et al, 1997; Durmer and Rosenquist, 2001; Klop et al, 2006; Lee and Hall, 2006).…”
Section: The Key To Collicular Functionmentioning
confidence: 99%